Effects of Nintendo Wii® program in dual-task performance in older adults - Rodrigues, Abel (2020)
A sedentary lifestyle has a strong impact on the older population; so participation in physical activity is important for enhanced physical and mental function, increasing health and well-being. In the elderly, dual-task activities are severely impaired which is why the Nintendo Wii® may be an important tool to maintain the proper functioning of the physical and mental levels among the elderly. This study sought to determine the effect of Nintendo Wii® training on dual-task performance, cognition, balance confidence, the health status and instrumental performances of daily life activities in older adults. A total of 18 participants aged 75.17±8.86 years were included. All participants were women, retired and living in their own residence. The training included a 15-minute exercise session using Wii®Fit twice a week for 8 weeks. The group was measured before and after the intervention (T0 and T1) and in 3 and 6 months follow-up (T2 and T3). Social demographic factors were assessed at T0 and T3. Cognition, general health status, confidence in balance, performance of instrumental activities of daily life, dual and multi-task performances were assessed at all evaluation moments. The mental component of health status and experimental protocol between T0 and T1 showed a statistically significant improvement. In T2 and T3 interval, there was a significant improvement in mental health status. From the baseline to T1, participants showed a statistical significant improvement in the mental component of health status and in experimental dual-task protocol. It can be concluded that the Nintendo Wii®Fit training program significantly improved dual and multi-task performances among older adults.